Comparison of Activity of Commercial Protective Cultures and Thermophilic Lactic Acid Bacteria against Listeria monocytogenes: A New Perspective to Improve the Safety of Sardinian PDO Cheeses - Maria Pina Meloni; Francesca Piras; Giuliana Siddi; Daniela Cabras; Eleonora Comassi; Roberta Lai; Olivia McAuliffe; Enrico Pietro Luigi De Santis; Christian Scarano (Foods, 2023)
Listeria monocytogenes contamination that occurs during and post-processing of dairy products is a serious concern for consumers, and bioprotective cultures can be applied to control the growth of the pathogen in sheep milk cheeses. However, to respect specifications provided for protected designation of origin (PDO) cheeses, only autochthonous microorganisms can be used as bioprotective cultures in these products. This in vitro study aimed to evaluate thermophilic lactic acid bacteria (LAB) isolated from sheep milk as bio-preservative agents to control L. monocytogenes growth in PDO cheese. Results were compared with those obtained with a commercial protective culture (cPC) composed of a Lactiplantibacillus plantarum bacteriocin producer designed to inhibit L. monocytogenes growth in cheese. The in vitro antilisterial activities of n.74 autochthonous LAB and a cPC were tested against 51 L. monocytogenes strains using an agar well diffusion assay. In addition, 16S rRNA sequencing of LAB isolates with antilisterial activity was conducted and strains of Lactobacillus helveticus, Lactobacillus delbrueckii subsp. indicus, Lactobacillus delbrueckii subsp. sunkii, Lactobacillus delbrueckii subsp. lactis and Enterococcus faecalis were identified. In this study, 33.6% (74/220) bacterial strains isolated from milk had characteristics compatible with thermophilic LAB, of which 17.6% (13/74) had in vitro antilisterial activity. These results demonstrate that raw sheep milk can be considered an important source of autochthonous thermophilic LAB that can be employed as protective cultures during the manufacturing of Sardinian PDO cheeses to improve their food safety. The use of bioprotective cultures should be seen as an additional procedure useful to improve cheese safety along with the correct application of good hygienic practices during manufacturing and the post-processing stages.